REWARDING TOP MANAGERS IN THE BANKING SECTOR DURING THE COVID 19 PANDEMIC - Ilic, Milos; Lepojevic, Vinko (The European Journal of Applied Economics, 2022)
The paper analyzes the practice of the leading banks in Europe related to the compensation of top managers during the COVID 19 pandemic and the determination of their relationship with the achieved performance of the banks. The paper aims to examine whether top managers' compensation was related to the bank's performance during the COVID 19 pandemic as well as give recommendations related to rewarding top managers in crises, based on the good practice of leading European banks during the COVID19 pandemic. By applying correlation and regression analysis methods, to a sample of leading 50 banks in Europe and 123 top managers, we examined the relationship between gross profit and compensation of top managers in 2020 and 2021. The results showed that the relationship between bank performance and top managers' compensation (base salary, bonus, and total compensation) was positive even during the COVID 19 pandemic.
Keywords: top management, basic salary, bonuses, total compensation, bank performance